2020
DOI: 10.1177/1090198120922120
|View full text |Cite
|
Sign up to set email alerts
|

The Campus Sexual Assault Policy and Prevention Initiative: Findings From Key Informant Interviews

Abstract: Addressing the widespread problem of sexual assault in college environments requires both prevention programming and policies addressing sexual misconduct in institutions of higher education. Through the Campus Sexual Assault Policy and Prevention Initiative, nine programs funded by the Office on Women’s Health approached this problem within a network of eight to 13 campuses apiece, supported by national organizations and local task forces. Near the close of the 3-year project period (June 2016–June 2019), key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Certain student populations are at increased risk of experiencing SVSH, including women (U.S. Department of Justice, 2014, 2017), first-year students (Krebs et al, 2016), students of color (Backman et al, 2020), LGBTQ + students (Coulter et al, 2017; Coulter & Rankin, 2020; Whitfield et al, 2018), those living with a disability (Bonomi et al, 2018), and international students (Bonistall Postel, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain student populations are at increased risk of experiencing SVSH, including women (U.S. Department of Justice, 2014, 2017), first-year students (Krebs et al, 2016), students of color (Backman et al, 2020), LGBTQ + students (Coulter et al, 2017; Coulter & Rankin, 2020; Whitfield et al, 2018), those living with a disability (Bonomi et al, 2018), and international students (Bonistall Postel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…University efforts to incorporate these strategies vary substantially, but generally include providing SVSH counseling, increasing student health services, building bystander intervention programs (Amar et al, 2014; Coker et al, 2011; Potter et al, 2009), establishing safe spaces, 5 training campus police, university staff, and faculty on survivor-centered prevention and care, implementing advocacy and legal assistance programs, creating social media campaigns, and enforcing alcohol and substance use policies (Clinton-Sherrod et al, 2011; Dills et al, 2016; Flensner & Von der Lippe, 2019). Campus-based activities perceived as successful by campus staff include: training in healthy masculinity, healthy relationships, and bystander intervention; hosting intercampus conferences open to all students; and celebrating and highlighting awareness days and months related to SVSH (e.g., Consent Day, Sexual Assault Awareness Month); and first-year orientation programming (Backman et al, 2020). Eisenberg and colleagues surveyed 28 universities and found that those with higher quantities of SVSH resources (e.g., paid office staff dedicated to SVSH, awareness events, support groups, counseling, and pamphlets and posters around campus) are associated with better mental health outcomes (e.g., less anxiety, PTSD) for SVSH survivors (Eisenberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions, there is little research on best ways to engage with students with campus policy information (Potter et al, 2016). Although effective campus SV policies are needed, the development of such is often a time-and labor-intensive process requiring IHE investment, implementation and compliance are often problematic, and outcomes are long-term (Backman et al, 2020;Bellis et al, 2018). Accordingly, it is important to shift the focus from campus-level policies to state-and national-level policies that can collectively work to prevent campus SV.…”
Section: Policy Levelmentioning
confidence: 99%
“…Despite the growing evidence base that there is a complex bidirectional relationship between alcohol use and sexual violence (Shorey et al, 2015; Testa & Cleveland, 2017), most sexual violence and alcohol use interventions are implemented separately (Abbey et al, 2002). Although brief clinical interventions show promise in addressing both binge drinking and risk for sexual violence (Gilmore et al, 2015), interventions that rely on provider delivery are challenging to implement in busy clinical settings (Miller et al, 2021), and campus prevention interventions often take place via one-time offerings provided during a student's first year orientation—limiting their usefulness in providing meaningful and nuanced content (Backman et al, 2020; Bonar et al, 2022; Klein et al, 2021).…”
mentioning
confidence: 99%